Waterpipe smoking: prevalence and associated factors among Jazan University students, Kingdom of Saudi Arabia - Bahri, Ahmed A.; Gosadi, Ibrahim M.; Mahfouz, Mohamed S.; Albasheer, Osama B.; Mawkili, Yahya H.; Mawkili, Hamzah A.; Yaqoub, Hassan A.; Alwan, Ahmed K.; Jawahy, Mohammed A.; Jabbari, Osama M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Waterpipe (WP) smoking exposes smokers to high levels of tobacco and toxins. This investigation is aiming to assess the prevalence of WP smoking among Jazan University students and to related influencing factors. Methods: This is a cross-sectional study. Multistage random sampling was utilized to target several colleges in Jazan University. Data were collected using a self-administered questionnaire where information about demographics, knowledge, attitude, and practice were collected. Chi square test and T Students test were used to assess statistical difference of measured variable among studied groups. Results: A total of 610 Jazan University students were recruited in this survey. The prevalence of students who had ever tried WP smoking (even once) was 52% and the proportion of participants who were current smokers at the time of recruitment was 34%. Being a male student, older than 21, related to health speciality and non-smoker was found to have a higher level of knowledge concerning WP smoking. A higher proportion of smokers were found to agree that WP smoking made them more attractive, agree that smoking WP is cheaper than cigarettes and agree that flavoured WP is less harmful than unflavoured WP when compared to non-smokers. Influence of gender smoking practice was apparent where most female student smokers were found to prefer to smoke with friends but not in the home or a cafe. Conclusions: The prevalence of WP smoking detected among Jazan University students was relatively high which mandates appropriate implementation of educational health campaigns with targeting influencing social determinants.